Collaborative protein filaments - Ghosal, Debnath (EMBO J, 2015)
It is now well established that prokaryotic cells assemble diverse proteins into dynamic cytoskeletal filaments that perform essential cellular functions. Although most of the filaments assemble on their own to form higher order structures, growing evidence suggests that there are a number of prokaryotic proteins that polymerise only in the presence of a matrix such as DNA, lipid membrane or even another filament. Matrix-assisted filament systems are frequently nucleotide dependent and cytomotive but rarely considered as part of the bacterial cytoskeleton. Here, we categorise this family of filament-forming systems as collaborative filaments and introduce a simple nomenclature. Collaborative filaments are frequent in both eukaryotes and prokaryotes and are involved in vital cellular processes including chromosome segregation, DNA repair and maintenance, gene silencing and cytokinesis to mention a few. In this review, we highlight common principles underlying collaborative filaments and correlate these with known functions.